The role of endothelial TRP channels in age-related vascular cognitive impairment and dementia - Negri, Sharon; Sanford, Madison; Shi, Helen; Tarantini, Stefano (Frontiers in Aging Neuroscience, 2023)
Transient receptor potential (TRP) proteins are part of a superfamily of polymodal cation channels that can be activated by mechanical, physical, and chemical stimuli. In the vascular endothelium, TRP channels regulate two fundamental parameters: the membrane potential and the intracellular Ca2+ concentration [(Ca2+)i]. TRP channels are widely expressed in the cerebrovascular endothelium, and are emerging as important mediators of several brain microvascular functions (e.g., neurovascular coupling, endothelial function, and blood–brain barrier permeability), which become impaired with aging. Aging is the most significant risk factor for vascular cognitive impairment (VCI), and the number of individuals affected by VCI is expected to exponentially increase in the coming decades. Yet, there are currently no preventative or therapeutic treatments available against the development and progression of VCI. In this review, we discuss the involvement of endothelial TRP channels in diverse physiological processes in the brain as well as in the pathogenesis of age-related VCI to explore future potential neuroprotective strategies.